Penggunaan Media Sosial Marketing Pada PT. Malak Kosmetik Indonesia - Nurinsani, Abdulwafi; Nurendah, Yulia; Noor, TB. Dicky Faldy Syahid (Program Vokasi dan LPPM IBI Kesatuan, 2024)
The development of the cosmetics industry in Indonesia continues to increase every year, this does not rule out the possibility of competition between competitors, companies must be able to keep up with the competition in order to survive in the tight competition, one strategy that can be used in the current digital era is by utilizing Social Media as one of the platforms for companies as a medium for carrying out promotional and advertising activities, as one of the company's efforts to stay connected with consumers so that they can compete with competitors. The purpose of this study is to find out: 1) how to implement the use of social media at PT. Malak Cosmetics Indonesia; 2) what are the obstacles in the use of social media at PT. Malak Cosmetics Indonesia; 3) how to overcome obstacles in the use of social media at PT. Malak Cosmetics Indonesia. The results of this study are: 1) The implementation of the use of social media at PT. Malak Cosmetics is going quite well, as evidenced by the occurrence of sales both online and offline; 2) The obstacles that occur are the lack of facilities and infrastructure owned.; 3) Other obstacles regarding community guidelines on nudity, pornography, or explicit sexual content owned by all social media platforms. Keyword: Social Media Marketing